Coal fragmentation studies in a fluidized bed - Pecson, Ferdinand A. (1988, 1988)
Coal fragmentation experiments were performed in a 0.3m internal diameter by 2.1m high fluidized bed combustor equipped with a solids sampling probe. A 200g batch of 3.0 to 6.9mm coal particles was charged into the hot combustor, and after 90s bed samples were taken at 1 min intervals until burn-off. The samples were immediately quenched with sand, and the burned coal particles were separated from the bed material by screening. Three coals were tested - Texas lignite, Montana sub-bituminous and Colorado bituminous coal. The bed material was 0.4mm silica sand and the fluidizing velocity was 1.8m/s. The effect of reducing the fluidizing velocity to 0.9 m/s and the effect of using 0.8mm aluminum oxide bed material were also investigated. The separated coal particles were sized with a microscope and weighed. Changes in burned coal particle size distribution with residence time were determined and for the case of Montana coal, were compared with the predictions of a combined char burning and attrition model. Microphotographs of the particles were taken to study changes in surface characteristics of the chars.
Results indicate that for all three types of coal there was an immediate shift of the major fraction of the particles from the 5.0-5.9mm size range to the0-1.9mm size range. after 90s there was a 290% increase in number of particles for the Montana sub-bituminous, 130% increase for Colorado bituminous and 200% increase for Texas lignite. Subsequent fragmentation varied for each coal. Reducing the fluidizing velocity and changing to a coarser sand did not significantly alter the fragmentation patterns.Comparison of the actual predicted size distribution curves showed that fragmentation during char burn is confined to mostly to the larger particles. The sizes of the resulting fragments can be obtained by determining which portions of the actual size distribution curve were above the predicted curve. The measured reactivities of the chars varied from 0.1 to 0.3 mg/cm^2/s depending on coal type. The lignite chars were the most reactive followed by the sub-bituminous and then the bituminous chars. Changing to a coarser bed material significantly increased the measured reactivities if the sub-bituminous and lignite chars. The densities of the the char which were also measured did not show any significant changes with burn time. The measured average char densities were 0.8 mg/mm^3 for Colorado bituminous, 0.91 mg/mm^3 for Montana sub-bituminous and 0.71 mg/mm^3 for Texas lignite. Microphotographs of the partially burned coal particles show numerous fracture planes and distinctly different surface features between the three different chars.
Thesis (Ph.D.Energy Engineering)--University of the Philippines Diliman.
Typescript.
Keywords: Coal -- Combustion; Fluidized-bed combustion